'Suspect Categories, ' Alienation and Counterterrorism: Critically Assessing PREVENT in the UK. Issue 4 (18th May 2020) - Taylor, Joel David
ABSTRACT: The 'suspect community' thesis has been a primary tool for exploring counter-terrorism strategies like the UK's PREVENT and their effect on communities. However, in seeking to shed light on the differentialist, complex nature of modern counter-terrorism, it was recently redesigned by Ragazzi as the 'suspect category' thesis. This article engages with this thesis' concept of distinguished 'risky' and 'trusted' suspect categories defining PREVENT's counter-terrorism engagement with Muslim communities. With the author's own reservations about this thesis, this article also explores this important concept to critically assess PREVENT as a counter-terrorism strategy. Principally, it provides an exploration of PREVENT's construction of risky and trusted suspect categories and their potential for fostering alienation, as well as a reflection on the effects of alienation on counter-terrorism. These discussions prove that PREVENT fosters alienation that is detrimental to counter-terrorism efforts. Damaging constructions as such not only make PREVENT redundant, but are also emblematic of Jackson's theory of the epistemological crisis of counter-terrorism, as this article will discuss. Recommendations regarding rethinking the conceptual basis for PREVENT will be also made with a specific emphasis on addressing the epistemological crisis of counter-terrorism.